Reaction of 2,2,4,4-tetrakis(trifluoromethyl)-1,3-dithiethane with N-vinyl compounds - Petrov, Viacheslav A.; Marshall, Will (Beilstein Journal of Organic Chemistry, 2013)
The reaction of hexafluorothioacetone dimer (2,2,4,4-tetrakis(trifluoromethyl)-1,3-dithiethane, 1) with vinylamides leads to the rapid formation of [2 + 2] cycloadducts: 4-amino-2,2-bis(trifluoromethyl)thietanes. The reaction proceeds in polar solvents (DMF, DMSO) in the absence of a catalyst at elevated temperature producing the corresponding cycloadducts in 47–86% yield. The reaction of N-vinylimidazole unexpectedly led to the formation of the corresponding 1-(hexafluoroisopropyl)-3-vinyl-1,3-dihydro-2H-imidazole-2-thione (5). The structure of this compound, along with the structures of two new thietanes was confirmed by single crystal X-ray diffraction.
Keywords: 1-(hexafluoroisopropyl)-3-vinyl-1,3-dihydro-2H-imidazole-2-thione; 2,2,4,4-terakis(trifluoromethyl)-1,3-dithiethane; 4-amino-2,2-bis(trifluoromethyl)thietanes; organo-fluorine

(untitled) - Middleton, W. J. (J. Org. Chem., 1965)

(untitled) - Middleton, W. J. (J. Org. Chem., 1965)

(untitled) - Petrov, V. A.; Marshall, W. (J. Fluorine Chem., 2010)

(untitled) - Kitazume, T.; Otaka, T.; Takei, R.; Ishikawa, N. (Bull. Chem. Soc. Jpn., 1976)

(untitled) - Petrov, V. A.; Marshall, W. (J. Fluorine Chem., 2012)

(untitled) - Kitazume, T.; Ishikawa, N. (Chem. Lett., 1973)

(untitled) - Petrov, V. A.; Marshall, W. (J. Fluorine Chem., 2011)

(untitled) - Petrov, V.; Marshall, W. (J. Fluorine Chem., 2007)

(untitled) - Petrov, V. A.; Krespan, C. G.; Marshall, W. (J. Fluorine Chem., 2005)

(untitled) - Raasch, M. S. (J. Org. Chem., 1970)

(untitled) - Petrov, V. A.; Marshall, W. (J. Fluorine Chem., 2012)

(untitled) - Petrov, V. A.; Marshall, W. J. (J. Fluorine Chem., 2009)

SHELXTL Sofware Suite, Version 6.0 (Bruker Axes Corp., 1996)